ZEOLIT CRACKING CATALYST - A.S. Nasution; E. Jasjfi; Evita H. Legowo (Testing Center for Oil and Gas LEMIGAS, 2003)
Nowadays, refiners are facing a continuing need to add bottom processing by catalytic process (catalytic cracking and hydro cracking processes) capacity a result of gradually deteriorating crude oil quality and flat-to-declining for residualfuel oil.